Sensitivity of CESEE countries’ export of differentiated products to exchange rate changes - Đorđević Zorić, Aleksandra (Industrija, 2020)
The research aims to examine the effects of exchange rate changes on the value of bilateral export of differentiated products in the selected CESEE countries, while controlling the impact of traditional gravity variables. Identifying the determinants that affect the export of high value-added products is of particular importance for this group of countries, while analyzing the effects of exchange rate changes is a contribution to the previous researches. In order to comprehensively understand the relationship between the observed variables, a quantile panel regeression was used to estimate the gravity equation. Examining the heterogeneity of the impact of exchange rate changes and other selected trade factors along the export distribution is another contribution of the paper, given that bilateral trade researches are usually based on assessing the average impact. The results indicate that the CESEE countries’ export of differentiated products is significantelly influenced by exchange rate changes. Exchange rate volatility has a negative impact, which grows at higher levels of export. The heterogeneity of the impact depending on export level was also confirmed for other determinants discussed in the paper.
Keywords: exchange rate volatility, exchange rate misalignment, export, gravity model, quantile panel regression